(untitled) (Asian Journal of Current Engineering and Maths, 2013)
The aim of this paper is to introduceÂ a new class of sets called Ï€gr-closed sets in topological spaces and to study their properties. Further , we define and study Ï€gr-continuity, Ï€gr-irresolute maps andÂ Ï€gr-T1/2-Space.Â Mathematics Subject Classification: 54A05